2008
DOI: 10.1016/j.jacc.2007.10.029
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Feature-Tracking Echocardiographic Method for the Quantitation of Regional Myocardial Function

Abstract: Velocity Vector Imaging, a new feature-tracking method, can accurately assess regional myocardial function at the endocardial level and is a promising clinical tool for the simultaneous quantification of regional and global myocardial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
197
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(208 citation statements)
references
References 15 publications
4
197
1
6
Order By: Relevance
“…compared to standard STI technology in that it has a smaller region of interest and combines ultrasound speckle with border tracking, 21 thereby enabling the tracking of endocardial (ENDO) and epicardial (EPI) motion separately. This capability allows independent quantification of myocardial deformation in ENDO and in EPI layers of LV, providing the opportunity to evaluate and estimate the physiological ENDO to EPI functional gradient.…”
Section: Myocardial Deformations In Amyloidosis and Hcmmentioning
confidence: 99%
“…compared to standard STI technology in that it has a smaller region of interest and combines ultrasound speckle with border tracking, 21 thereby enabling the tracking of endocardial (ENDO) and epicardial (EPI) motion separately. This capability allows independent quantification of myocardial deformation in ENDO and in EPI layers of LV, providing the opportunity to evaluate and estimate the physiological ENDO to EPI functional gradient.…”
Section: Myocardial Deformations In Amyloidosis and Hcmmentioning
confidence: 99%
“…3,4) In these myocardial deformations, diastolic left ventricular (LV) abnormalities are sensitive early signs of myocardial ischemia and have the additional advantage of persisting longer than ischemic-induced systolic dysfunction, [5][6][7] indicating diastolic strain might be superior to systolic strain for detecting the deformation of the myocardial ischemia area. Some previous studies [8][9][10] reported that peak systolic longitudinal strain (PSLS) was useful for detecting CAD at rest.…”
mentioning
confidence: 99%
“…Strain assessment by this method was validated in an animal study against sonomicrometry. 9 Longitudinal systolic velocity, strain, and SR were recorded for lateral, septal, anterior, and inferior walls for each patient. Each wall was divided into basal, mid, and apical segments automatically.…”
Section: Velocity Vector Imagingmentioning
confidence: 99%